2018
DOI: 10.1039/c8cp04075c
|View full text |Cite
|
Sign up to set email alerts
|

Nature of halogen bonding involving π-systems, nitroxide radicals and carbenes: a highlight of the importance of charge transfer

Abstract: The adiabatic ALMO-EDA analyses indicate that charge transfer is important in accurate description of halogen bonding (XB) involving π-systems, nitroxide radicals and carbenes as XB acceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 67 publications
1
30
0
Order By: Relevance
“…In our previous works, we concluded that isolated benzene···X 2 dimers adopt the η 2 (over‐bond) binding mode and noted that η 1 (over‐atom) binding mode is very close in energy as compared to the former . Hence, AR‐type XBs are rim‐specific.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In our previous works, we concluded that isolated benzene···X 2 dimers adopt the η 2 (over‐bond) binding mode and noted that η 1 (over‐atom) binding mode is very close in energy as compared to the former . Hence, AR‐type XBs are rim‐specific.…”
Section: Resultsmentioning
confidence: 92%
“…Recently, we highlighted the importance of π‐type XBs in an extensive crystallographic database search and elucidated their intriguing site specificity . Along with several other groups, we also emphasized the importance of charge transfer interactions in obtaining accurate interaction energies and XB geometries . In order to accelerate the process of material discovery and to reduce the number of experimental trial‐and‐error cycles, it is important to utilize computational chemistry and physics tools tactfully in directing experiments.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the molecular orbital interaction provides a proper description of the charge transfer contribution in XB formation. Various energy decomposition analyses showed strong supporting evidence for the role of charge transfer [8][9][10]. In particular, the frontier orbital interaction explains the site specificity of XB involving aromatic XB-acceptors, while the electrostatic model based on ESP fails to explain the site specificity [5].…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been employed to investigate observable shifts induced by intermolecular binding, such as the red or blue shifts in vibrational frequencies upon the formation of hydrogen or halogen bonds. [44][45][46][47][48] However, it has not been made generally possible yet to separate the observable effects of forward/backward CT in a manner that is similar to how the ALMO-CTA identifies the A→B and B→A contributions for a pair of fragments A and B, 9 even though such a partition is highly desirable in particular for interpretation purposes. One early exception was the already mentioned CSOV approach, which employed full SCF for one fragment in the field of e.g.…”
Section: Introductionmentioning
confidence: 99%